Povezanost suvremenih tehnologija prijevoza na području Podunavlje- Jadran - Rudić, Dušan (Promet - Traffic&Transportation, 2012)
The study of combined modern transport technologies in the Danube-Adriatic region refers us to the conclusion of major significance of transport corridors and freight flows and relative lagging behind of surface transport as a whole. Particular reference has been drawn to the low level of development of transversal traffic routes crossing the territory of the Republic of Croatia on the route from the Danube Region to the Adriatic Region. Without constitution of modern railway lines and highways to be integrated into the European TER and TEM systems it shall not be possible to complete the traffic related evaluation or promote the Adriatic Orientation policy of the Republic of Croatia. The model of linkage and modernization of surface and sea transport involves the modernization of the overall technological and traffic infrastructure, and introduction of modern information system(s) to enable linkage of all participants in traffic on the Danube-Adriatic corridor.